Keeping the University Free and Growing. - Donovan, Herman Lee, 1887-1964 (The University Press of Kentucky, 1959)
During the fifteen years of Herman L. Donovan's presidency (1941-56), the University of Kentucky entered a new era of maturity as an educational institution. The period was characterized by many administrative crises, such as those arising from the flood of veteran students following World War II, the rapidly rising costs of maintenance and expansion, and the apathy or active opposition of many Kentuckians to the concept of a free and developing university. Nevertheless, during this same period tremendous advances, both in material assets and in the less tangible qualities of academic life, wer.